COMPARING THE LEGAL RULES (AHKAM-I SHARIAH) IN THE MALIKI AND SHAFII SCHOOLS WITH THE HANAFI SCHOOL OF THOUGHT - Hyder Gulam (Islam Futura, 2016)
This paper is about the legal rules (ahkam-i shariah) in Maliki and Shafi schools, as compared with the Hanafi school of thought (or madhabs). This paper will define certain terms and briefly provide an overview of these schools of law (noting that there are four main Sunni schools of law). It should be noted that ahkam-i shar'iyaa falls within the generic rubric of fiqh. Fiqh deals with putting the Message of Islam into practice and involves both rulings about acts of worship which derive directly from Allah's revelation to His Prophet Muhammad (pbuh) in the book or the Sunnah. When the various schools appeared, they did not compel anyone to follow them should an individual not agree with one of their judgments. This paper will also posit that the differences amongst the schools is but an inherent mercy from God.